Develop and test a micropump based on acoustic impedance mismatch - Nur Farah Izzah Muhammad Segar (Nanyang Technological University, 2020)
This Final Year Project (FYP) report presents a study on valveless impedance pumps and these micropumps function based on the concept of acoustic impedance mismatch. Using two closed-loop system models, this project investigates the performance of the impedance pump by examining the changes in flow rate and flow direction of the fluid in the system in response to a change in various parameters such as actuator position, current and frequency of the actuator and compression exerted by the actuator. The performance of the micropump was tested on two separate models - a two-dimensional planar closed-loop system as well as a three-dimensional set up. Each system consists of both elastic and rigid tubes and these two materials of different impedances create a mismatch that drives the flow of the fluid in the system. A compression beam, serving as an actuator, acts at an asymmetric point along one of the elastic tubes and this periodic deformation of the flexible tube results in flow movement of the fluid in the system. A microfiber indicator is used to track the flow rate and direction in the closed-loop system model. The results and data collected from this study resemble findings reported from open literatures. Maximum flow rate was achieved when the actuator acts at a point furthest from the midway of the elastic tube, and this flow rate peaked at the resonant frequency of 20Hz for the two-dimensional model and 15Hz for the three-dimensional model. Contrary to most studies, flow direction was observed moving from the shorter to longer portion of the elastic tube, but flow reversal was detected at higher frequencies between 30Hz to 40Hz. These discrepancies were later confirmed to be attributed to the low current supplied to the actuator.